PERKEMBANGAN TATA BUSANA TARI PERSEMBAHAN DI KOTA BATAM - Nathania, Ivena (Jurnal Seni Tari, 2020)
Malay land has many artistic treasures, one of which is the Persembahan Dance. The dance, which is also known as the Sekapur Sirih Dance, is a welcoming dance. With the development of the times, the Persembahan Dance also developed from sharing aspects. One aspect is the Persembahan Dance costume. Many innovations made by the people of Batam, including the studio. However, unfortunately these innovations can fade the authenticity of the Persembahan Dance costume. Malay government and institutions also paid less attention to the dance costumes of Persembahan. The purpose of this research is to provide information about the development of the Persembahan of Dance costumes in Batam. In addition, please note that the function of dance costumes is correct in the community. Research sources are obtained from photographs, videos, personal documents, websites, memos or notes. In this study, researchers also used the function of dance sociology according to MC. Neil Lowny. In using the Persembahan Dance costume, everyone should be able to uphold their authenticity more. Keywords : Development, Persembahan Dance, Dance Costume of Persembahan